Demand Stimulus as Social Policy - Auerbach, Alan J; Gorodnichenko, Yuriy; Murphy, Daniel (Review of Economic Studies, 2026)
Abstract We exploit a panel of city-level data with rich demographic information to estimate the distributional effects of Department of Defense spending and its effects on a range of social outcomes. The income and employment generated by defence spending accrue predominantly to households without a bachelor's degree. These households as well as Black and Hispanic households tend to disproportionately benefit from this spending. Defence spending also promotes a range of beneficial social outcomes that are often targeted by government programs, including reductions in poverty, divorce rates, disability rates, and mortality rates, as well as increases in homeownership rates, health insurance rates, and occupational prestige. We compare the effects of defence spending with the effects of general demand shocks and explore reasons for the differential effects of the shocks.